2018
DOI: 10.4067/s0718-18762018000100107
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivation of Information Infrastructures for International Trade: Stakeholder Challenges and Engagement Reasons

Abstract: The development of information infrastructures for international trade to improve supply chain visibility and security has gained momentum due to technological advances. An information infrastructure is a shared, open, and evolving assemblage of interlinked information systems providing distinct information technology capabilities. Examples of information infrastructures are the internet, electronic market places and music platforms. Information infrastructures can be highly beneficial as shown by the aforemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We believe that in future research it is important to incorporate new metrics for calculating engagement to provide a deeper analysis and new statistical analysis for the study of specific areas of engagement in social networks. It is also interesting to the study of engagement, in contexts outside normality, so it could be applied in the current health context (COVID-19) to identify the similarities and differences in the social networks of this wine industry, highlighting the increase in electronic commerce [72,73]. However, the application of this indicator is applied in the social networks of any industry to make comparisons between companies in different industries.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that in future research it is important to incorporate new metrics for calculating engagement to provide a deeper analysis and new statistical analysis for the study of specific areas of engagement in social networks. It is also interesting to the study of engagement, in contexts outside normality, so it could be applied in the current health context (COVID-19) to identify the similarities and differences in the social networks of this wine industry, highlighting the increase in electronic commerce [72,73]. However, the application of this indicator is applied in the social networks of any industry to make comparisons between companies in different industries.…”
Section: Discussionmentioning
confidence: 99%
“…Involving almost 150 respondents in the sample, he examined the following factors: salary, other benefits, appraisal, job security, responsibility, etc. He concluded that there are no significant differences in these areas between the two generations [3].…”
Section: B Working Patterns Of Generation Ymentioning
confidence: 99%
“…Third, it then follows that DI innovation typically emerges through the semi-coordinated actions of actors with partially diverging interests that are trying to shape the infrastructure towards specific ends (Knol and Tan, 2018; Zorina and Dutton, 2021). Since it is rarely possible to redesign a DI from scratch, actors that want to innovate a DI must take what currently exists – that is, the constituent components of the DI conceptually referred to as the ‘installed base’ (Aanestad et al, 2017; Rodon and Eaton, 2021) – and try to evolve it in a desired direction (Ciborra and Hanseth, 2000; Koutsikouri et al, 2018).…”
Section: Regulation and Digital Infrastructuresmentioning
confidence: 99%
“…Within the DI literature, the role of governmental regulation can be understood in relation to the innovation activities that can be completed to modify a DI (Knol and Tan, 2018). In DIs, a degree of decentralised control is critical to innovation (Ciborra and Hanseth, 2000;Hanseth and Modol, 2021) since it allows for bottom-up innovation driven by self-reinforcing processes centred on repurposing technology (Yoo et al, 2010;Hanseth and Modol, 2021).…”
Section: Regulation and Digital Infrastructure Innovationmentioning
confidence: 99%